Pengembangan Tes Bahasa Arab Menggunakan Aplikasi Wondershare Quiz Creator di STIT Bustanul Ulum Lampung Tengah - Muhammad Abdun Jamil (At Turots: Jurnal Pendidikan Islam, 2024)
The rapid advancement of educational technology has transformed Arabic language testing. This study explores the use of Wondershare Quiz Creator at STIT Bustanul Ulum, offering an efficient, interactive tool for modernizing test creation and improving language proficiency assessment.. The foundation of this research arises from the increasing demand for effective and engaging assessment methods in language education, especially within the realm of higher education, where interactive and dynamic evaluation tools are becoming essential. Traditional paper-based tests often lack the dynamic and engaging elements necessary to effectively assess students’ language skills in the modern era. By integrating technology into the assessment process, teachers can offer more comprehensive, diverse, and engaging evaluations. An  aims this research to create a test programs that harnesses the power of Wondershare Quiz Creator, an intuitive and interactive platform designed to craft quizzes that evaluate multiple facets of language proficiency, including speaking, reading, and writing skills. This tool allows for multiple question types—ranging from multiple-choice to essay and true/false questions—enabling a more flexible and adaptive evaluation of students' skills. The research methodology involved a developmental approach, which included stages of designing, developing, and implementing the test. Data was collected through a combination of literature review, needs analysis, and practical trials in the classroom. Participants consisted of students from the Arabic language program at STIT Bustanul Ulum, and the tests were administered through the Wondershare Quiz Creator platform. The effectiveness of the test was measured based on student performance and feedback, as well as teacher evaluations of the tool's ease of use and functionality.The findings showed that using Wondershare Quiz Creator greatly enhanced student engagement and performance in Arabic language assessments. The application's interactive features enabled students to comprehend the questions more effectively and respond with greater ease. Further research is recommended to explore the long-term impact of this tool on student achievement and to enhance its effectiveness in diverse educational settings.